BAURAN KEBIJAKAN MONETER DAN MAKROPRUDENSIAL BANK INDONESIA SEMENJAK MARET 2011 HINGGA MARET 2012 - Sihono, Teguh; Yusof, Rohaila (Jurnal Economia, 2012)
Abstract: Monetary Policy and Macroprudential of Bank Indonesia 2011-2012. Indonesia economic growth since February 2011 until the fourth quarter of 2011 was 6.5%. Throughout the year of 2011, CPI inflation has declined from 6.65 % in March to 4.15% in December. Investment increased in early 2012 in line with the development of infrastructure, reduction in the BI rate thus providing a favorable climate and positive perceptions for investors. In the first two quarters of 2011, export exceeded import, but in the fourth quarter of 2011, there was a deficit in the balance of payment as import increased. In early 2011, Indonesia foreign exchange reserve amounted to US $99.6 billion, which increased in August to US $124.6 billion. At the end of January 2012 the foreign exchange reserves increased by $US 112 billion. Performance of financial market and banking was fairly steady in February 2011 further demonstrated by the CAR above 8% and gross NPL below 8%, while credit growth of 24.6%  of this state wake up to early 2012. Keywords: economic growth, balance of payment, BI rate, inflation Abstrak: Bauran Kebijakan Moneter Dan Makroprudensial Bank Indonesia Semenjak Maret 2011 Hingga Maret 2012. Pertumbuhan ekonomi Indonesia sejak Februari 2011 sampai kuartal keempat tahun 2011 adalah 6,5%. Sepanjang tahun 2011, inflasi IHK turun dari 6,65% pada Maret menjadi 4,15% pada Desember. Terjadi peningkatan investasi di awal 2012 seiring dengan pembangunan infrastruktur, penurunan BI rate sehingga memberikan iklim yang kondusif dan persepsi positif bagi investor. Dalam dua kuartal pertama tahun 2011, ekspor mampu melebihi impor namun pada kuartal keempat tahun 2011, terjadi defisit dalam neraca pembayaran akibat impor meningkat. Pada awal 2011, cadangan devisa Indonesia sebesar US $ 99,6 miliar, yang meningkat pada Agustus menjadi US $ 124,6 miliar. Pada akhir Januari 2012 cadangan devisa meningkat sebesar US $ 112 miliar. Kinerja pasar keuangan dan perbankan cukup stabil pada Februari 2011 lebih lanjut ditunjukkan oleh CAR di atas 8% dan NPL gross di bawah 8%, sementara pertumbuhan kredit sebesar 24,6% baru terjadi pada awal 2012. Kata Kunci: pertumbuhan ekonomi, neraca pembayaran, suku bunga BI, inflasi